Cyprus in World War II - Yiangou, Anastasia. (London ; New York, NY)
xxii, 240 sayfa, [8] sayfa resim
Keywords: “World War II marked a pivotal point in the history of Cyprus, yet surprisingly, this period of the island's history has been little studied to date. Anastasia Yiangou here provides the first major study of the impact of World War II on the political development of Cyprus. In doing so she traces shifting Cypriot attitudes to the war and the formation of a triangular conflict in the island between the Left, Right and British colonial power. She explains how the British and Cypriots fought a war alongside each other, yet remained far apart in discussions on the future of the island. Yiangou's original and compelling analysis highlights how the post-1945 landscape of Cypriot political struggles was shaped by forces set in motion during the war itself“ --